Development and preliminary validation of a pain scale for ophthalmic pain in horses: The Equine Ophthalmic Pain Scale (EOPS). (December 2021) - Ortolani, F.; Scilimati, N.; Gialletti, R.; Menchetti, L.; Nannarone, S.
Highlights: Equine Ophthalmic Pain Scale (EOPS) showed excellent inter–intra-observer reliability. EOPS demonstrated differences between healthy horses and horses with ophthalmic diseases. The optimal cut-off to identify ophthalmic disease was a Total Score ≥ 7. Changes in EOPS after surgical/medical treatment confirmed its responsiveness. The elimination of some items could improve internal consistency. Abstract: The purpose of this study was to describe the development and preliminary validation of a composite pain scale, called the Equine Ophthalmic Pain Scale (EOPS), to assess ocular pain in horses. Indicators associated with ocular pain were selected and classified as behavioural, physiological or ocular expressions. Eight horses diagnosed with ocular or adnexa diseases that required medical or surgical treatment were enrolled in the study (group P). The developed EOPS was applied at the baseline (T0) and 1 week later (T7). Moreover, the EOPS was applied twice, 1 week apart, to 15 healthy control horses (group C). Videos of 60−80 s duration of all assessments were retrospectively analysed by seven masked observers, who scored items included in the behavioural and ocular expression categories of the EOPS. The inter- and intra-observer reliability was excellent (intraclass correlation coefficients ≥0.75) for most of the scored items. Cronbach's alpha (0.76) indicated that the EOPS had good internal consistency. The total score (TS), calculated as the sum of all scores, differed between groups C and P at T0 ( P < 0.001) and reduced after medical/surgical treatment in group P ( P = 0.017), indicating the responsiveness of the EOPS. Moreover, the area under the curve (AUC=0.918, 95% confidence interval = 0.815–1.000; P < 0.001) indicated that the EOPS was very accurate for distinguishing healthy from pathological animals. Sensitivity and specificity of EOPS to identify horses with ocular pathology (at the optimal cut-off, i.e. TS ≥ 7) were 81.3% and 100.0%, respectively. However, 'overall behaviour', 'position inside the box', 'ear movements' and 'head position' items as well as physiological parameters, showed sub-optimal reliability, consistency and/or item-total correlation, suggesting that there is still room to improve this composite scale.